THE OPSONIZATION TEST IN BRUCELLOSIS - TOVAR MANCERA, RAUL (Laboratorio Fisiologia General y Vegetal, CD MEXICO, DF, MEX, 1975)
Leucochloridium insigne and Notocotylus pacifera are descr
J IMMUNOL VIRUS RES EXP CHEMOTHER
Keywords: OPSONIZATION, TEST, BRUCELLOSIS; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA